INOVASI PEMBELAJARAN DI DALAM BUKU AJAR KIMIA SMA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Hendra Gunawan Parulian; Manihar Situmorang (LPPM Universitas Negeri Medan, 2013)
Abstract Learning innovation of chemistry textbook to improve students achievement of senior high school students is explained. The study is carried out through development of innovative textbook, standardization to meet the standard textbook requirement based on BNSP and UNESCO standar, and implementation of the textbook as learning media in the class. Text book development is conducted to enrich chemistry materials based on the curriculum followed by innovation by integrating teaching method and learning media into the textboox. The developed textbook is the standarized by expert judgement. Finally the innovated textbook is then used as learning media on the teaching of chemistry to year XI senior high school students. The research showed that learning innovation into the textbook has successfully been done. Innovated textbook is found very effective to improve students achievemen in chemistry. Students achievement in experimental class which were taught by innovated textbook is found higher thatn that in control class that are taught by ordinary references. The students are interested to use innovated textbook. Innovated textbook is able to bring students to study independently and bring them moving from teacher centre learning into students centre learning